Capturing structure and function in an embryonic heart with biophotonic tools - Karunamuni, Ganga H.; Gu, Shi; Ford, Matthew R.; Peterson, Lindsy M.; Ma, Pei; Wang, Yves T.; Rollins, Andrew M.; Jenkins, Michael W.; Watanabe, Michiko (Frontiers in Physiology, 2014)
Disturbed cardiac function (flow, excitation, contraction, calcium transients) at an early stage of development has been shown to correlate with and may lead to cellular/molecular, functional and structural cardiac anomalies at later stages culminating in the congenital heart defects (CHDs) that present at birth. It is not surprising that cardiac function, which drives embryonic and extraembryonic circulation, is also connected to neural and placental development. While our knowledge of molecular and cellular steps in cardiac development is growing rapidly, our understanding of the role of cardiovascular function in the embryo is still rudimentary. One reason for the scanty information in this area is that the tools to study early cardiac function are limited. Recently developed and adapted Biophotonic tools may overcome the challenges of studying the tiny fragile beating heart. In this chapter, the strengths and limitations of Biophotonic tools will be described with emphasis on Optical Coherence Tomography (OCT). OCT can be used for detailed structural and functional studies of the tubular and looping avian embryo heart under physiological conditions. The same hearts can be subsequently rapidly and quantitatively phenotyped at a later stage using OCT. When combined with other tools such as Optimal Mapping (OM) and Optical Pacing (OP), OCT has the potential to reveal in spatial and temporal detail the biophysical changes that can potentially impact mechanotransduction pathways. This information may provide better explanations for the etiology of the CHDs when interwoven with our understanding of the multiple molecular pathways that have been described to be involved. Examples of application of these tools to study the etiology of CHDs are presented. Directions for future directions and advances in the use of Biophotonic tools are discussed.